Reseña/Review (Assange, J., Appelbaum, J., Müller-Maguhn, A., Zimmermann, J., "Cypherpunks", Barcelona: Deusto, ISBN: 9788423416394, 192 págs., 2013) - Mateo Regueiro, Estela (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2014)
Reseña/Review (Assange, J., Appelbaum, J., Müller-Maguhn, A., Zimmermann, J., "Cypherpunks", Barcelona: Deusto, ISBN: 9788423416394, 192 págs., 2013)